Impact of Climate Change on Traditional Agricultural Practices: An Ethnoecological Perspective - Yohanes Kamakaula (West Science Agro, 2024)
This research discusses the impact of climate change on traditional agricultural practices from an ethnoecological perspective. Through a literature review method, we analyzed various relevant sources to understand the complexity of the relationship between humans, the environment, and culture in the context of global climate change. Findings indicate that climate change poses serious challenges to the sustainability of traditional agricultural systems, such as changing weather patterns, vulnerability of agricultural ecosystems, and loss of local knowledge. However, local knowledge also offers significant adaptation potential in facing climate change, with the integration of traditional knowledge and modern science being key to developing effective adaptation strategies. In conclusion, this research highlights the importance of understanding and preserving the sustainability of traditional agricultural practices in the era of climate change.